Ligand coordination modulates reductive elimination from aluminium(iii). Issue 35 (17th August 2016) - Urwin, Stephanie J.; Rogers, David M.; Nichol, Gary S.; Cowley, Michael J.
Abstract : Oxidative addition to low-valent main-group centres is a major class of reactivity for these species. Here, we present a mechanistic study of the much rarer reverse process – reductive elimination – in Al(iii ) systems, and unravel ligand effects in this process. Abstract : Oxidative addition of inert bonds at low-valent main-group centres is becoming a major class of reactivity for these species. The reverse reaction, reductive elimination, is possible in some cases but far rarer. Here, we present a mechanistic study of reductive elimination from Al(iii ) centres and unravel ligand effects in this process. Experimentally determined activation and thermodynamic parameters for the reductive elimination of Cp*H from Cp*2 AlH are reported, and this reaction is found to be inhibited by the addition of Lewis bases. We find that C–H oxidative addition at Al(i ) centres proceeds by initial protonation at the low-valent centre.